Two genetic variants in NEXN and ABCC6 genes found in a patient with right coronary artery to right ventricle fistula combined with giant coronary aneurysm and patent ductus arteriosus - Peng, Yongxuan; Ye, Jiajun; Xu, Yuejuan; Huang, Jihong; Wu, Yurong; Liu, Wei; Bai, Kai; Chen, Sun; Lu, Yanan (Frontiers in Cardiovascular Medicine, 2022)
Objective Coronary artery fistula, defined as communication between a coronary artery and a great vessel or a cardiac chamber, is a relatively rare anomaly with an estimated incidence of 0.002% in the general population. It could be combined with a giant coronary artery aneurysm, with an incidence of 5.9% of the total incidence rate of CAF in the general population. The pathogenesis of these two combined anomalies is not clear, and we aimed to detect whether genetic abnormalities underlie the pathogenesis of these rarely combined anomalies. Materials and methods A 6-year-old patient with a diagnosis of the right coronary artery to right ventricle fistula combined with a giant right coronary artery aneurysm and patent ductus arteriosus underwent a surgical repair at our center. The diagnosis was confirmed by echocardiography, CT, and surgery. DNA was extracted from the peripheral venous blood samples of the patient and his mother after informed consent was obtained. Hematoxylin and Eosin (HE) and Alizarin red staining were performed on the excised coronary artery aneurysm. Exome sequencing and in silico analyses were performed to detect detrimental genetic variants. Results No obvious abnormalities were found in the excised coronary artery aneurysm. A heterozygous truncated variant (NM_144573: c.G298T; p.G100X) in the NEXN gene and a missense variant (NM_001171: c.G1312A; p.V438M) in the ABCC6 gene were carried by the patient but not by his mother. Conclusion The NEXN-truncated variant, NEXN-G100X, is associated with the development of coronary arteries and congenital coronary artery anomalies.